The effect of social media on body image, self-esteem, and social appearance anxiety among young adults - Badola, Ankita; Arora, Niharika; Saran, Brijesh; Priyanka (International Journal of Research in Medical Sciences, 2025)
Background: Social media usage is growing rapidly among young adults, influencing body image, self-esteem, and appearance-related anxiety. Aim was to assess the relationship of social media usage with body image, self-esteem, and social appearance anxiety among young adults. Methods: A cross-sectional study was conducted among 404 college students at Santosh Medical College and Hospital during the M.Sc. Clinical Psychology program. Purposive sampling was used. Tools included the social media use scale, Rosenberg self-esteem scale, body image satisfaction rating scale, and social anxiety questionnaire for adults (SAQ-A30). Data were collected using standardized procedures. Descriptive statistics (mean, standard deviation) were used to assess participant characteristics. Chi-square tests were used to examine the association between social media use and psychological variables. Data were analyzed using SPSS version 23 and MS Excel. Results: There was a highly significant association between social media usage and all three psychological variables: body image dissatisfaction (χ2=297.99, p<0.01), low self-esteem (χ2=46.57, p=0.027), and social appearance anxiety (χ2=293.43, p<0.01). Social media usage (χ2=302.14, p<0.01) was strongly linked to poorer mental health outcomes. Conclusions: The study highlights the psychological risks of high social media engagement among young adults. It reveals a significant relationship between social media use and body image dissatisfaction, low self-esteem, and high social appearance anxiety. Media literacy, mental health awareness, and promoting healthy online behaviour are essential for mitigating these effects.